Education Can Improve Community Participation in the Control of Dengue Haemorrhagic Fever in Cicadas and Babakan Penghulu Village, Bandung City, a Case of Participation Measurement Using the Method of Arnstein - Sri Indriyani; Juli Soemirat (Universitas Airlangga, 2020)
Introduction: According to the Ministry of Health, cases of dengue haemorrhagic fever (DHF) increased from 2 to 34 provinces during 46 years, hence, Indonesia had not been able to control DHF. While specific drugs and vaccines against DHF virus are not yet available, the only way to control DHF is by controlling the vector. Sustainable Development Goals (SDG's) program on vector borne diseases requires a reduction of mortality by 75% and incidences by 60% in 2030. Vector control in Indonesia is being done through community participation such as draining, closing, and recycling used goods, and activities to avoid mosquito bites known as